The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00441-020-03332-4
|View full text |Cite
|
Sign up to set email alerts
|

CCN2/CTGF promotor activity in the developing and adult mouse eye

Abstract: CCN2/CTGF is a matricellular protein that is known to enhance transforming growth factor-β signaling and to induce a myofibroblast-like phenotype in a variety of cell types. Here, we investigated Ccn2/Ctgf promotor activity during development and in the adult mouse eye, using CTGFLacZ/+ mice in which the β-galactosidase reporter gene LacZ had been inserted into the open reading frame of Ccn2/Ctgf. Promotor activity was assessed by staining for β-galactosidase activity and by immunolabeling using antibodies aga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 86 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…In situ results of this study show that there is a direct connection between biomechanical load and the expression of CCN2/CTGF in astrocytes of the ONH region. The astrocytes of the prelaminar region of the glial lamina site showed a strong signal for the CCN2/CTGF promoter activity, whereas the astrocytes of the postlaminar region and the retinal astrocytes exhibit only a faint staining ( Dillinger et al, 2021 ). Our findings clearly support that astrocytes can sense mechanical cues in their ambient substratum and react on biomechanical alterations of the surrounding environment with changes in GFAP, vimentin and CCN2/CTGF synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ results of this study show that there is a direct connection between biomechanical load and the expression of CCN2/CTGF in astrocytes of the ONH region. The astrocytes of the prelaminar region of the glial lamina site showed a strong signal for the CCN2/CTGF promoter activity, whereas the astrocytes of the postlaminar region and the retinal astrocytes exhibit only a faint staining ( Dillinger et al, 2021 ). Our findings clearly support that astrocytes can sense mechanical cues in their ambient substratum and react on biomechanical alterations of the surrounding environment with changes in GFAP, vimentin and CCN2/CTGF synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both effects continue to increase with increasing age ( Junglas et al, 2012 ). Recently we could show that astrocytes are the cellular source of CCN2/CTGF in the murine ON and ONH ( Dillinger et al, 2021 ). A detailed analysis of the CCN2/CTGF distribution in the ONH of glaucomatous eyes is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Weiss et al demonstrated that the glutamatergic synapse controlled apoptosis and the degeneration of different retinal cells induced by CTGF [ 172 ]. Furthermore, glutaminolysis promotes the apoptosis resistance of IPF fibroblasts through the epigenetic regulation of XIAP and survival [ 173 ].…”
Section: Ctgf Drives Senescence In Ipfmentioning
confidence: 99%
“…Further evidence in mice shows that the astrocytic levels of CTGF in the ONH increases in glaucomatous animals as a result of elevated IOP and stiffness, which agrees with the observation that there are elevated levels of CTGF in glaucomatous ONHs of humans as well [ 68 ]. At least in mice, CTGF seems to be predominantly expressed by astrocytes in the ONH [ 69 ], but there is reason to suggest that CTGF may affect other cell types such as LC cells [ 37 ].…”
Section: Glial Cellsmentioning
confidence: 99%